1989
DOI: 10.1105/tpc.1.8.747
|View full text |Cite
|
Sign up to set email alerts
|

Pectic Cell Wall Fragments Regulate Tobacco Thin-Cell-Layer Explant Morphogenesis.

Abstract: Pectic fragments of cell wall polysaccharides, released from the walls of suspension-cultured sycamore cells by treatment with endopolygalacturonase, were tested for morphogenesis-regulating activity in a modified tobacco thin-cell-layer explant (TCL) bioassay (D. Mohnen, S. Eberhard, V. Marfa, N. Doubrava, P. Toubart, D. J. Gollin, T.A. Gruber, W. Nuri, P. Albersheim, and A. Darvill, manuscript submitted). The pectic fragments inhibited the formation of roots on TCLs grown on a root-inducing medium containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…To date, there is limited information regarding their eVect on vegetative shoot formation in cultured explants. As reported by Eberhard et al (1989), pectic fragments, applied at 10 g l ¡1 to a medium containing 4 M indolebutyric acid and 0.5 M kinetin, inhibited root formation in tobacco thin cell layers, but induced the formation of a few Xoral or vegetative shoots. However, under diVerent hormonal conditions (1.5 M indolebutyric acid plus 0.8 M kinetin), the same pectic fragments supplied at various concentrations, including 10 g l ¡1 , enhanced the formation of Xowers, while leaving vegetative shoot formation poor.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…To date, there is limited information regarding their eVect on vegetative shoot formation in cultured explants. As reported by Eberhard et al (1989), pectic fragments, applied at 10 g l ¡1 to a medium containing 4 M indolebutyric acid and 0.5 M kinetin, inhibited root formation in tobacco thin cell layers, but induced the formation of a few Xoral or vegetative shoots. However, under diVerent hormonal conditions (1.5 M indolebutyric acid plus 0.8 M kinetin), the same pectic fragments supplied at various concentrations, including 10 g l ¡1 , enhanced the formation of Xowers, while leaving vegetative shoot formation poor.…”
Section: Introductionsupporting
confidence: 62%
“…In addition, OGs exhibit growth regulatory eVects on cell elongation (Branca et al 1988), on de novo Xower (Eberhard et al 1989;Marfà et al 1991), root (Bellincampi et al 1993(Bellincampi et al , 1996, and on stomata formation (Altamura et al 1998b) in cultured tobacco explants. To date, there is limited information regarding their eVect on vegetative shoot formation in cultured explants.…”
Section: Introductionmentioning
confidence: 99%
“…Suspension-cultured tobacco (Nicotiana tabacum L. cv. Samsun) cells, originally isolated from pith callus tissue (Eberhard et al 1989), were grown on Murashige and Skoog (1962) medium supplemented with 4.5 lM 2,4-dichlorophenoxyacetic acid and 90 mM sucrose, and subcultured every 13±14 d (Doong et al 1995).…”
Section: Methodsmentioning
confidence: 99%
“…In-vitro bioassays have con®rmed that pectic oligomers function as biological signals that stimulate a wide array of defence responses, ranging from early events at the cell surface to the subsequent biosynthesis of defence molecules such as phytoalexins, pathogenesis-related (PR) proteins, proteinase inhibitors, lignin (Coà te and Hahn 1994), and hydroxyprolinerich glycoproteins (Boudart et al 1995). In addition, it has been shown that these oligomers also regulate development and growth (Eberhard et al 1989;MarfaÁ et al 1991). Although active fragments are generally oligogalacturonides with a degree of polymerization (DP) of galacturonic acid (GalA) of 9±15, more-complex galacturonides can also act as elicitors (Brecht and Huber 1988).…”
Section: Introductionmentioning
confidence: 99%